ANALISIS KOMPETENSI PROFESIONAL DOSEN FAKULTAS TARBIYAH DAN KEGURUAN UIN SULTAN SYARIF KASIM RIAU - Mimi Hariyani (Jurnal Pesona Dasar, 2022)
The importance of the existence of a college is inseparable from the quality of the college. To achieve good quality, there are at least three components that must be possessed by a university, the first individual is both the lecturer and the education personnel, the two are the managers such as the head of the study program, the dean to the rector, and the third is the system within the institution itself. This study is motivated by the importance of the quality of lecturers, especially the professional competence they have for the achievement of good quality from UIN Sultan Syarif Kasim Riau. The purpose of this study is to describe the state of professional competence lecturers Faculty of Tarbiyah and teacher UIN Sultan Syarif Kasim Riau. This study is a descriptive analysis conducted through survey method by spreading a questionnaire to collect research data. Population in this research is all lecturer of Faculty of Tarbiyah and Teacher Training UIN Suska Riau, As for the number of population studied are as many as 189 people, consisting of 160 permanent civil servants and 29 lecturers non civil servants. While the sample taken in the study amounted to 65 people. Based on the result of the study, it can be concluded that the professional competence of lecturer by using subvariabel duty and lecturer's responsibility based on seven indicators, they are: conducting education, conducting study, implementing community service, increasing and developing academic qualification, objective acting, And maintain and nurture the unity and unity of the nation shows that of 65 lecturers, there are 58 lecturers or 89.23% who have professional competence in the good category. This is also indicated by the average score for the professional competence of this lecturer is 83.74 or is in the good category.